SARS-CoV-2 and cancer: Are they really partners in crime?. (September 2020) - van Dam, Peter A.; Huizing, Manon; Mestach, Gino; Dierckxsens, Stazie; Tjalma, Wiebren; Trinh, Xuan Bich; Papadimitriou, Kostantinos; Altintas, Sevilay; Vermorken, Jan; Vulsteke, Christof; Janssens, Annelies; Berneman, Zwi; et al.
Highlights: Cancer patients with COVID-19 have a higher morbidity and mortality. Particularly patients with ongoing or recent cancer treatment, metastatic solid tumors and hematological malignancies are at risk. Underlying immunosuppression, elevated cytokine levels, altered expression of the angiotensin converting enzyme (ACE-2) and TMPRSS2, and a prothrombotic status in cancer patients may fuel the effects of a SARS-CoV-2 sepsis. The gene expression level of ACE2 may be an indicator of the susceptibility to SARS-CoV-2 infection, while TMPRSS2 plays a supporting role. Better knowledge of the mechanisms involved may be a tool to identify high risk patients and to prevent severe complications by targeting the involved pathways. Abstract: The outbreak of the SARS-CoV-2 pandemic has overwhelmed health care systems in many countries. The clinical presentation of the SARS-CoV-2 varies between a subclinical or flu-like syndrome to that of severe pneumonia with multi-organ failure and death. Initial reports have suggested that cancer patients may have a higher susceptibility to get infected by the SARS-CoV-2 virus but current evidence remains poor as it is biased by important confounders. Patients with ongoing or recent cancer treatment for advanced active disease, metastatic solid tumors and hematological malignancies are at higher risk of developing severe COVID-19 respiratory disease that requires hospitalization and have a poorer disease outcome compared to individuals without cancer. However it is not clear whether these are independent risk factors, or mainly driven by male gender, age, obesity, performance status, uncontrolled diabetes, cardiovascular disease and various other medical conditions. These often have a greater influence on the probability to die due to SARS-CoV-2 then cancer. Delayed diagnosis and suboptimal cancer management due to the pandemic results in disease upstaging and has considerable impact cancer on specific death rates. Surgery during the peak of the pandemic seems to increase mortality, but there is no convincing evidence that adjuvant systemic cancer therapy and radiotherapy are contraindicated, implicating that cancer treatment can be provided safely after individual risk/benefit assessment and some adaptive measures. Underlying immunosuppression, elevated cytokine levels, altered expression of the angiotensin converting enzyme (ACE-2) and TMPRSS2, and a prothrombotic status may fuel the effects of a SARS-CoV-2 in some cancer patients, but have the potential to be used as biomarkers for severe disease and therapeutic targets. The rapidly expanding literature on COVID-19 should be interpreted with care as it is often hampered by methodological and statistical flaws.